Efficacy of nano silver dressings over conventional dressings in chronic wounds - Suhas, K.; Manvi, P. Manvi Naga (International Surgery Journal, 2018)
Background: Chronic wounds give rise to serious health problems, accompanied by a decrease in quality of life. Silver has been an effective agent with documented efficacy against wide spectrum of bacterial, viral, and fungal infections. Recently, many silver-based preparations are available for effective management of wounds. Among them silver nano particles, exhibit significantly novel and distinct physical, chemical, and biological properties. Due to their nano scale size, they have been elicited much interest in wound management. This study aims to compare the efficacy of nano silver dressing in chronic wounds with that of conventional dressings. Methods: This was a prospective study conducted in the Department of General Surgery, Alluri Sita Rama Raju Academy of Medical Sciences from August 2017 to August 2018. A total of 100 patients with chronic wounds were included in the study and were equally divided into-Study group and Control group randomly. Swab cultures were sent in all the patients. The study group received nano silver dressings while the controls received daily dressings with normal saline soaked gauges, betadine and hydrogen peroxide. Data regarding the time required for healing, number of days required for healing and percentage of healing are noted. Results: Nano silver dressings in the treatment of chronic wounds are found to be safe, effective, promoter of wound healing, promotes epithelization, accelerates healing, eliminates anaerobes and breaks microbial synergy more effectively than conventional dressing. Hence Nano silver spray prove to be more effective in the management of chronic wounds. In study group, 50% of patients stay for 3-4 weeks whereas in control group, 70% of patients stay for 5-6 weeks. 91-99% reduction in size of ulcer is seen in 43 out of 50 patients in study group whereas in control group only 8 out of 50 shows 91-99% reduction in size. Conclusions: Nano silver dressings is a cost effective option in ulcer management. It decreases the period of hospitalization and reduces the burden on the health care system.